Comparison of hemodynamic, clinicopathologic, and gastrointestinal motility effects and recovery characteristics of anesthesia with isoflurane and halothane in horses undergoing arthroscopic surgery - Durongphongtorn, Sumit; McDonnell, Wayne N.; Kerr, Carolyn L.; Teixeira Neto, Francisco José [UNESP]; Mirakhur, Kuldip K. (American Veterinary Medical Association (AVMA), 2006)
Objective - To compare hemodynamic, clinicopathologic, and gastrointestinal motility effects and recovery characteristics of halothane and isoflurane in horses undergoing arthroscopic surgery. Animals - 8 healthy adult horses. Procedure - Anesthesia was maintained with isoflurane or halothane (crossover study). At 6 intervals during anesthesia and surgery, cardiopulmonary variables and related derived values were recorded. Recovery from anesthesia was assessed; gastrointestinal tract motility was subjectively monitored for 72 hours after anesthesia. Horses were administered chromium, and fecal chromium concentration was used to assess intestinal transit time. Venous blood samples were collected for clinicopathologic analyses before and 2, 24, and 48 hours after anesthesia. Results - Compared with halothane-anesthetized horses, cardiac index, oxygen delivery, and heart rate were higher and systemic vascular resistance was lower in isoflurane-anesthetized horses. Mean arterial blood pressure and the dobutamine dose required to maintain blood pressure were similar for both treatments. Duration and quality of recovery from anesthesia did not differ between treatments, although the recovery periods were somewhat shorter with isoflurane. After isoflurane anesthesia, gastrointestinal motility normalized earlier and intestinal transit time of chromium was shorter than that detected after halothane anesthesia. Compared with isoflurane, halothane was associated with increases in serum aspartate transaminase and glutamate dehydrogenase activities, but there were no other important differences in clinicopathologic variables between treatments. Conclusions and clinical relevance - Compared with halothane, isoflurane appears to be associated with better hemodynamic stability during anesthesia, less hepatic and muscle damage, and more rapid return of normal intestinal motility after anesthesia in horses undergoing arthroscopic procedures.
Keywords: aspartate aminotransferase; chromium; diazepam; dobutamine; glutamate dehydrogenase; halothane; halothane bp; isoflo; isoflurane; ketamine; romifidine; anesthesia induction; anesthetic recovery; animal experiment; arthroscopic surgery; aspartate aminotransferase blood level; bleeding; blood pressure regulation; blood sampling; cardiopulmonary hemodynamics; controlled study; enzyme activity; feces analysis; female; femoral nerve; gastrointestinal motility; general anesthesia; heart index; heart rate; hemodynamics; horse; intestine transit time; liver injury; maintenance drug dose; male; mean arterial pressure; muscle injury; nonhuman; pathology; preoperative care; preoperative evaluation; systemic vascular resistance; venous blood; veterinary medicine; Analysis of Variance; Anesthesia, Inhalation; Animals; Arthroscopy; Gastrointestinal Motility; Halothane; Heart Function Tests; Horses; Isoflurane; Pulmonary Ventilation; Animalia; Equidae; Equus caballus